Immunization against East Coast Fever. Report of a workshop - Irvin, A.D. (International Laboratory for Research on Animal Diseases, 1986)
This report presents the proceedings of a workshop which was held to discuss the most appropriate ways of collecting, handling and analysing data on the performance and productivity of cattle immunized against East Coast Fever (ECF). This workshop was a sequel to one held in 1984 in which the different methods of immunization against ECF were discussed. In the first session reports and results from field trials were presented. In all cases, emphasis was placed on approaches to immunization and data collection and analysis rather than specific results. The second session considered in more detail design of immunization trials and programmes, and the ways different computer programmes could be used for handling, storing and processing data. In the final session, the various aspects of performance and productivity recording and evaluation were examined, and recommendations were presented.